Proceedings of the Fourteenth Annual ACM Symposium on Parallel Algorithms and Architectures 2002
DOI: 10.1145/564870.564901
|View full text |Cite
|
Sign up to set email alerts
|

Optimal tiling for the RNA base pairing problem

Abstract: Dynamic programming is an important combinatorial optimization technique that has been widely used in various fields such as control theory, operations research, computational biology and computer science. Many authors have described parallel dynamic programming algorithms for the family of multistage problems. More scarce is the literature for the more general class of problems where dependences appear between non-consecutive stages. Among the important problems falling in this class is the RNA base pairing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…For current machines it is an unrealistic approximation. Inspired by the blocking technique, F. Almeida [4] proposed a parallel implementation with tiling on a ring of processors. They showed the usefulness of the tiling technique for this nonuniform dependence DP.…”
Section: Related Workmentioning
confidence: 99%
“…For current machines it is an unrealistic approximation. Inspired by the blocking technique, F. Almeida [4] proposed a parallel implementation with tiling on a ring of processors. They showed the usefulness of the tiling technique for this nonuniform dependence DP.…”
Section: Related Workmentioning
confidence: 99%
“…The main difficulty for obtaining an efficient parallel implementation on distributed memory multicomputers system is to find a good balance between communication and computation costs. [J. H. Chen and Maizel 1998][F. Almeida and Gonzalez 2002] represent parallel implementations of RNA secondary structure prediction DP algorithm. In [J. H. Chen and Maizel 1998] the computational load balance is satisfactory but their designs do not optimize the communication cost.…”
Section: Figurementioning
confidence: 99%
“…The authors proved experimentally that the communications took about 50% of the execution time for a sequence with length of more than 9212. In [F. Almeida and Gonzalez 2002] the authors described blocked parallel implementation on a ring of processors and showed the usefulness of the tiling technique for this nonuniform dependences DP. They focused on reducing the communication costs.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations